On knowing and not knowing in the anthropology of medicine - Littlewood, Roland (Walnut Creek, CA : Left Coast Press, 2007)
Social scientific studies of medicine typically assume that systems of medical knowledge are uniform and consistent. But while anthropologists have long rejected the notion that cultures are discrete, bounded, and rule-drive entities, medical anthropology has been slower to develop alternative approaches to understanding cultures of health. This provocative volume considers the theoretical, methodological, and ethnographic implications of the fact that medical knowledge is frequently dynamic, incoherent, and contradictory, and that and our understanding of it is necessarily incomplete and part.
The importance of knowing about not knowing / Murray Last -- Coconuts and syphilis : an essay in overinterpretation / Roland Littlewood -- On "medical system" and questions in fieldwork / Gilbert Lewis -- Explanatory models and oversystematization in medical anthropology / Simon Dein -- The ambivalence of integrative medicine / Guido Giarelli -- Not knowing about defecation / Sjaak van der Geest -- Christianity, tradition, AIDS, and pornography : knowing sex in western Kenya / P. Wenzel Geissler and Ruth J. Prince -- Feeling and borderlinking in Yaka healing arts / Ren Devisch -- On knowing and not knowing in Latvian psychiatric consultations / Vieda Skultans -- Farewell to fieldwork? : constraints in anthropological research in violent situations / Els van Dongen -- Neutralizing the young : the South African Truth and Reconciliation Commission and youth / Pamela Reynolds -- In touch without touching : Islam and healing / David Parkin.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Medical anthropology; Traditional medicine -- Cross-cultural studies; Anthropology; Medicine, Traditional; Cross-Cultural Comparison; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Medical anthropology; Traditional medicine; Medizin; Anthropologie; Electronic books; Cross-cultural studies